2021
DOI: 10.12911/22998993/135945
|View full text |Cite
|
Sign up to set email alerts
|

Using Allometric Equations to Estimate Mangrove Biomass and Carbon Stock in Demta Bay, Papua Province, Indonesia

Abstract: The mangrove ecological services as carbon sinks and storage are very useful in the efforts to mitigate global warming and climate change. In this study, the above and below-ground biomass, carbon stock, as well as carbon sequestration by the mangroves in Demta Bay, Papua Province, Indonesia were estimated. Allometric equations were used to determine the mangrove biomass in 36 observation plots. The biomass value was used to determine carbon stock and estimate carbon sequestration. Nine mangrove species were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 18 publications
(25 reference statements)
1
7
0
4
Order By: Relevance
“…These highest value of CO 2 absorption was linear with the number of individuals invented (232 individual), volume (66.49 m 3 ha), as well as AGB (907.52 Mg ha -1 ) (Zulhalifah et al 2021). The same result has been found by Indrayani et al (2021) who revealed that the average CO 2 emission from the atmospheric at mangrove ecosystem of Demta Bay was 319.37±124.92 Mg CO 2 ha -1 . Harishma et al (2020) also found the similar result in which the CO 2 absorption (513.13 Mg CO 2 /ha) was much higher than this research.…”
Section: Carbon Stock and Co 2 Absorption By A Lanatasupporting
confidence: 86%
See 2 more Smart Citations
“…These highest value of CO 2 absorption was linear with the number of individuals invented (232 individual), volume (66.49 m 3 ha), as well as AGB (907.52 Mg ha -1 ) (Zulhalifah et al 2021). The same result has been found by Indrayani et al (2021) who revealed that the average CO 2 emission from the atmospheric at mangrove ecosystem of Demta Bay was 319.37±124.92 Mg CO 2 ha -1 . Harishma et al (2020) also found the similar result in which the CO 2 absorption (513.13 Mg CO 2 /ha) was much higher than this research.…”
Section: Carbon Stock and Co 2 Absorption By A Lanatasupporting
confidence: 86%
“…The total of carbon stock which obtained in this research tends to be smaller than another research. Indrayani et al (2021) found that carbon stock of several mangrove species in Demta Bay, Papua, was much higher. These species was R. apiculata (100.81 Mg C ha -1 ), R. mucronata (61.25 Mg C ha -1 ), and B. gymorrhiza (47.14 Mg C ha -1 ).…”
Section: Carbon Stock and Co 2 Absorption By A Lanatamentioning
confidence: 95%
See 1 more Smart Citation
“…Meanwhile, the below-ground values in the middle and distal zones are 13.48 Mg ha -1 and 24.36 Mg ha -1 , respectively. The above and below-ground carbon stock in Demta Bay (Papua) is 87.1 ± 34.07 Mg ha -1 (Indrayani et al 2021). Compared to other forest types, the value of the above-ground carbon stock in conservation mangrove forests is also lower.…”
Section: Above-ground and Below-ground Carbonmentioning
confidence: 97%
“…Selain itu, ekosistem mangrove juga memiliki peranan yang sangat penting dalam memitigasi dampak perubahan iklim (Sharma et al, 2019;Indrayani et al, 2021). Analuddin et al, (2020) menyatakan bahwa ekosistem mangrove berperanan penting dalam penyuplai O 2 , dan mengabsorbsi CO 2 dari atmosfer.…”
Section: Pendahuluanunclassified